Social Aspect of Sustainable Development: Issues of Poverty and Food Shortage - Asta Mikalauskiene; Raminta Narutaviciute-Cikanauske; Ingrida Sarkiunaite; Dalia Streimikiene; Rumyana Zlateva (Montenegrin Journal of Economics)
Social aspect in the context of Sustainable development became more important, when it was realized that the level of poverty in the world is not decreasing. There is a need to investigate poverty conception as a separate element. It is important to understand the transformation road of poverty concept from original thought – lack of income for fulfilling basic physical needs, to the emphasizing on needs of individuals and life quality. Poverty is a multifaceted phenomenon, which can be caused by a variety of different reasons; it is also constantly changing, depending on how the countries and their societies are developing. Persons living in poverty are at the group of risk; individuals are more vulnerable, often have more frequent health problems, their resources and quality of life are generally lower than the national average. Object – social dimension of sustainabale development.